Genetic disease detection and DNA amplification using cloned thermostable ligase. - Barany, F (1991)
Polymerase chain reaction, using thermostable DNA polymerase, has revolutionized DNA diagnostics. Another thermostable enzyme, DNA ligase, is harnessed in the assay reported here that both amplifies DNA and discriminates a single-base substitution. This cloned enzyme specifically links two adjacent oligonucleotides when hybridized at 65 degrees C to a complementary target only when the nucleotides are perfectly base-paired at the junction. Oligonucleotide products are exponentially amplified by thermal cycling of the ligation reaction in the presence of a second set of adjacent oligonucleotides, complementary to the first set and the target. A single-base mismatch prevents ligation/amplification and is thus distinguished. This method was exploited to detect 200 target molecules as well as to discriminate between normal beta A- and sickle beta S- globin genotypes from 10-microliters blood samples.